2019
DOI: 10.3892/etm.2019.7782
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of CaMKII and Cx43 in a rat model of post‑stroke depression

Abstract: Expression of Ca 2+ /CaM-dependent protein kinase II (CaMKII) and connexin 43 (Cx43) in a rat model of post-stroke depression (PSD) was investigated. Rats were separated into control group (10 rats underwent a sham operation and were not ligated after incision), PSD group (13 PSD rats) and KN93 group (12 rats were treated with KN93, an inhibitor of CaMKII, on the basis of the PSD group). After PSD modeling, Longa scoring was performed, and an open field test as well as a step-through tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…These studies indicate that the Cx43 gap-junction protein and its pathway in the hippocampus can effectively alleviate depressive behavior induced by CUMS. Similarly, a decrease in Cx43 protein expression was observed in PSD rats (Tao et al 2019). Hippocampal Cx43 gap junctions play a considerable role in depression.…”
Section: Cx43 Gap-junction Channels Regulate Hippocampal Neuronal Pla...mentioning
confidence: 74%
See 1 more Smart Citation
“…These studies indicate that the Cx43 gap-junction protein and its pathway in the hippocampus can effectively alleviate depressive behavior induced by CUMS. Similarly, a decrease in Cx43 protein expression was observed in PSD rats (Tao et al 2019). Hippocampal Cx43 gap junctions play a considerable role in depression.…”
Section: Cx43 Gap-junction Channels Regulate Hippocampal Neuronal Pla...mentioning
confidence: 74%
“…CaMKII not only regulates LTP but also participates in the development of LTD by acting on GluA1 Ser567 (Coultrap et al 2014). Tao et al found that CaMKII expression was upregulated in the hippocampus of PSD rats and that the CaMKII inhibitor KN93 improved depressive behavior in PSD (Tao et al 2019). By studying the antidepressant effects of two cyclic enol ether terpene compounds, Zhang et al found that combined treatment with both compounds rapidly inhibited CaMKII phosphorylation and enhanced BDNF signaling, whereas injection of a CaMKII activator attenuated its antidepressant effects and BDNF expression .…”
Section: Camkii Regulates Ltd-related Mechanismsmentioning
confidence: 99%
“…Twenty-four hours following the sham/MCAO surgeries, rats were subjected to a neurological examination (Longa test) consisting of a six-point scale [ 33 ]: 0, no symptom; 1, Failure to extend left forepaw completely (shows mild focal neurological deficit); 2, circling/turning to one side while walking (moderate focal neurological deficit); 3, falling to one side while walking (indicates a severe focal neurological deficit); 4, loss of consciousness and no voluntary movement; and 5, death due to brain ischemia.…”
Section: Methodsmentioning
confidence: 99%
“…A gene was de ned as signi cantly associated with pseudotime if its estimated q value was lower than 0.01. Neurological de cit score Neurological de cits after 3 days of reperfusion in each mouse were evaluated with a 5-point scoring system using the Longa score test as previously described [24]. The scoring standards were as follows: 0 = no neurologic de cit; 1 = failure to extend the contralateral forepaw fully; 2 = circling to the contralateral side; 3 = falling over to the contralateral side; and 4 = no spontaneous locomotor activity.…”
Section: Pseudotime Analysismentioning
confidence: 99%